Fundamentals of organizational behavior : an applied approach - DuBrin, Andrew J. (South-Western College, 1997)
This book is divided into four parts: Introduction to Organizational Behavior; The Individual in the Organization; Groups and Intergroup Relations; and The Organizational System and the Global Environment.